Microbial Genomics as a Catalyst for Targeted Antivirulence Therapeutics - Sintchenko, Vitali; Timms, Verlaine; Sim, Eby; Rockett, Rebecca; Bachmann, Nathan; O'Sullivan, Matthew; Marais, Ben (Frontiers in Medicine, 2021)
Virulence arresting drugs (VADs) are an expanding class of antimicrobial treatment that act to ‘disarm’ rather than kill bacteria. Despite an increasing number of VAD being registered for clinical use, uptake is hampered by the lack of methods that can identify patients who are most likely to benefit from these new agents. The application of pathogen genomics can facilitate the rational utilisation of advanced therapeutics for infectious diseases. The development of genomic assessment of VADs targets is essential to support the crucial early stages of VADs diffusion into infectious disease management. Genomic identification and characterisation of VADs targets in clinical isolates can augment antimicrobial stewardship and pharmacovigilance. Personalised genomics guided use of VADs will provide crucial policy guidance to regulating agencies, assist hospitals to optimise the use of these expensive medicines and create market opportunities for biotech companies and diagnostic laboratories.